Penyuluhan Manfaat dan Pembuatan Serbuk Jamur Tiram dengan Metode Pemanasan Oven di Kelurahan Limau Manih Kota Padang - RIZAL, ROSIANA (LPPM Universitas Dharma Andalas, 2024)
Oyster mushrooms, which have broken and small leaf petals, if used with fast, precise and simple technology, can increase the economic value of farmers and can become an icon of regional products in Limau Manih Village, Padang City. Oyster mushrooms contain mevinolin and similar compounds which have the potential to inhibit HMG CoA in cholesterol biosynthesis, increasing metabolism; hepatitis, digestion, duodenum and stomach, treatment of high blood pressure, diabetes, anemia, increasing body resistance (polio, influenza, anemia), nutrition, anti-tumor, anti-oxidant, and regulating autonomic nervous function, with activity methods providing information about oyster mushrooms which has many health benefits so it can be processed into oyster mushroom powder for long-term use, as well as increasing the productivity of oyster mushroom powder by oven drying. The conclusion of this activity is that the ingredients match the needs so that it can improve the economy of oyster mushrooms and standardize flour as a food ingredient and traditional medicine. There was a positive response from the participants considering that this service activity was part of the partners' understanding of the properties of oyster mushrooms which are used as traditional medicine. Most (75%) participants understand the actions taken by partners to increase the production of quality oyster mushroom flour